2001
DOI: 10.1051/gse:2001123
|View full text |Cite
|
Sign up to set email alerts
|

Simulation analysis to test the influence of model adequacy and data structure on the estimation of genetic parameters for traits with direct and maternal effects

Abstract: Simulations were used to study the influence of model adequacy and data structure on the estimation of genetic parameters for traits governed by direct and maternal effects. To test model adequacy, several data sets were simulated according to different underlying genetic assumptions and analysed by comparing the correct and incorrect models. Results showed that omission of one of the random effects leads to an incorrect decomposition of the other components. If maternal genetic effects exist but are neglected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 28 publications
3
25
0
Order By: Relevance
“…This effect has been noted in other empirical and simulation based studies (e.g. Meyer, 1992;Clé ment et al, 2001), including work on the Soay sheep. For example, using a much reduced subset of the current data, Milner et al (2000) found that inclusion of a maternal permanent environment effect led to significantly lower estimates of heritability for female body size traits.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This effect has been noted in other empirical and simulation based studies (e.g. Meyer, 1992;Clé ment et al, 2001), including work on the Soay sheep. For example, using a much reduced subset of the current data, Milner et al (2000) found that inclusion of a maternal permanent environment effect led to significantly lower estimates of heritability for female body size traits.…”
Section: Discussionsupporting
confidence: 54%
“…It should be noted that data structure can have a major influence on the estimation of genetic parameters using the animal model (Clé ment et al, 2001;Maniatis & Pollott, 2003). For example, by analysing subsets of a larger database, Maniatis & Pollott (2003) found stronger negative values of r am for early growth traits in sheep when fewer dams (10% of those in the pedigree structure) contributed phenotypically informative records, and when the average number of offspring per dam was low (1 or 2).…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to the fact that in the present study the age of the birds at the time of measuring the traits was 17 to 18 wk, compared to an age of 5 to 6 wk in chickens. However, while this percentage may seem low, studies comparing models including and excluding maternal effects have shown that omission of the maternal effects may result in an overestimation of the direct heritability (e.g., Koerhuis and Thompson, 1997; Clément et al, 2001; Grosso et al, 2010). To evaluate the effect of the permanent environmental effect of the dam, all 4 models also were run without this effect, which resulted in increased heritabilities for the leg health traits in the range of 0.01 to 0.06.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to its shallowness, our current pedigree precludes the estimation of a maternal genetic variance. Consequently, the additive genetic variance may be biased upwardly to an unknown degree (Clé ment et al, 2001). Additive genetic variances and selection gradients may then be over-estimates.…”
Section: Current Limitationsmentioning
confidence: 99%